The Role of Oxidative Stress in Atopic Dermatitis - Nopriyati; Rina Novriani; Athuf Thaha; Sarah Diba; Yulia Farida Yahya; Inda Astri Aryani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Atopic dermatitis (AD) is a chronic skin inflammation found in children with a varied course caused by external and internal factors. The incidence of AD in industrialized countries is 10-20% in children and 1-3% in adults. The main etiopathogenesis of AD is genetic and skin barrier disorders, immunologic disorders, and environment. Oxidative stress (SO) is the accumulation of reactive oxygen species (ROS) that exceeds the defense capacity of the body's antioxidant system. Uncontrolled ROS production plays a major role in various skin diseases. Oxidative stress can damage the deoxyribonucleic acid (DNA) of keratinocytes through lipid oxidation, as well as disrupt skin barrier function, increase the production of proinflammatory cytokines and worsen AD lesions. The main objectives of this literature review are to determine the role of oxidative stress in AD and antioxidants as adjunctive therapy.